EVALUATION OF NOVEL SEED DRESSING FUNGICIDES FOR MANAGING MACROPHOMINA PHASEOLINA INDUCED ROOT ROT IN GREEN GRAM (Journal of Plant Disease Sciences, 2026)
Green gram (Vigna radiata L.) is an important pulse crop cultivated extensively in the arid and semi-arid tropics, where its productivity is frequently constrained by seed- and soil-borne fungal diseases. These pathogens adversely affect seed germination, seedling vigor, and plant establishment, resulting in significant yield losses. The present study was conducted to isolate and identify seed-borne fungal pathogens associated with green gram and to evaluate the efficacy of different fungicidal seed treatments under field conditions. Significant differences were observed among the seed treatments with respect to field emergence, seedling mortality, shoot length, root length, and dry matter production. All fungicidal seed treatments performed significantly better than the untreated control. Among the treatments, seed treatment with Penflufen + Trifloxystrobin @ 1 ml kg⁻¹ seed (T₁) proved to be the most effective, recording 88.25% field emergence, the lowest seedling mortality of 14.25%, 15.25%, and 17.25% at 15, 30, and 45 days after sowing (DAS), respectively, along with the highest shoot length (23.25 cm), root length (31.25 cm), and dry matter accumulation (7.00 g plant⁻¹) at 45 DAS. This was followed by seed treatment with Propiconazole 13.9% + Difenoconazole 13.9% EC @ 1 ml kg⁻¹ seed (T₃), which recorded 89.00% field emergence, seedling mortality of 18.75%, 21.75%, and 21.25% at 15, 30, and 45 DAS, respectively, and produced shoot length, root length, and dry matter of 17.75 cm, 29.50 cm, and 4.57 g plant⁻¹, respectively, at 45 DAS.
Keywords: Fungicides; Green gram; Management; Root rot